Línea de tiempo comparativa de historia de la arquitectura en Riobamba - Arregui Paredes, Ariana Paola (2021)
This research project shows the evolution of architecture in the city over time, from its creation to the present, reflecting this transformation through the description of buildings that were influenced by the events that occurred; these buildings are an important part of the architecture of the city. The research project is developed in six chapters, in the first chapter the research sources used for the basis of the thesis are explained, since having such a broad topic, it is necessary to organize the bibliography to be used; The second chapter begins with the history of architecture in the city, its beginnings from the time it was a village to becoming a city and how it was settled prior to the earthquake that devastated the city; The next chapter expresses what happened after the earthquake and how the city was rebuilt in a new place. This chapter shows the planning of the city and how it grew from this new settlement; In the fourth chapter it is detailed how the economic development was in the city after the arrival of the train, which would mark a beginning for the increase of the economy in the city; the fifth chapter recounts the events that took place in the country and their influence on the architecture of the city, since in this chapter, modern architecture appears and with it, representative buildings and nationally recognized architects; and finally, the sixth chapter details what is happening in the city in current times, what architecture is like today and the factors for the growth of the city. With all this information, the aim is to create a criterion about the importance of the inhabitants, the culture and the events that take place in a city for the evolution of architecture.